Growth and demography of the solitary scleractinian coral Leptopsammia pruvoti along a sea surface temperature gradient in the Mediterranean Sea. - Erik Caroselli; Francesco Zaccanti; Guido Mattioli; Giuseppe Falini; Oren Levy; Zvy Dubinsky; Stefano Goffredo (PLoS ONE)
The demographic traits of the solitary azooxanthellate scleractinian Leptopsammia pruvoti were determined in six populations on a sea surface temperature (SST) gradient along the western Italian coasts. This is the first investigation of the growth and demography characteristics of an azooxanthellate scleractinian along a natural SST gradient. Growth rate was homogeneous across all populations, which spanned 7 degrees of latitude. Population age structures differed between populations, but none of the considered demographic parameters correlated with SST, indicating possible effects of local environmental conditions. Compared to another Mediterranean solitary scleractinian, Balanophyllia europaea, zooxanthellate and whose growth, demography and calcification have been studied in the same sites, L. pruvoti seems more tolerant to temperature increase. The higher tolerance of L. pruvoti, relative to B. europaea, may rely on the absence of symbionts, and thus the lack of an inhibition of host physiological processes by the heat-stressed zooxanthellae. However, the comparison between the two species must be taken cautiously, due to the likely temperature differences between the two sampling depths. Increasing research effort on determining the effects of temperature on the poorly studied azooxanthellate scleractinians may shed light on the possible species assemblage shifts that are likely to occur during the current century as a consequence of global climatic change.